Trinity Cathedral, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Image depicts a view of the Trinity Cathedral, located in the capital city of Port of Spain, in the Republic of Trinidad and Tobago. This view of the southern elevation of the building is from the corner of Queen and Chacon Streets, looking northward.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings; Port of Spain; 1912